Neoadjuvant in breast cancer - Viola, Alberto (Cirugía del Uruguay, 1999)
In the conceptual area of systemic treatment for breast cancer, the authors point out the neoadjuvant strategy As biological background which sustains neoadjuvancy emphasis is put on the hypothesis of Goldie and Coldman, Fisher, and O'Reily which refer respective/y to resistant ce/fular clones, growth factors and liberation of angiostatic factors.